Regulation of Emotions in the Context of Islamic Religious Education and Modern Psychology - Nurfitroh, Fitriyani; Tihami, M.A; Hunainah, Hunainah; Bachtiar, Machdum; Wasehudin, Wasehudin; Lugowi, Rifyal Ahmad (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2025)
Emotion regulation plays a vital role in students' academic success and character development. This study examines emotion regulation strategies from the perspectives of Islamic education and modern psychology, aiming to identify their similarities, differences, and implications for intervention programs. Using qualitative analysis, the research reveals that while both approaches share the objective of enhancing individual well-being, they differ in methods and theoretical foundations. The integration of emotion regulation into educational practices through structured training and intervention programs has been shown to strengthen students' ability to manage their emotions, positively influencing their academic performance and character growth. The findings emphasize the significance of combining Islamic educational values with effective psychological strategies, as well as the necessity of community support in the emotion regulation process. This study offers recommendations for a comprehensive intervention program that not only enriches students' learning experiences but also equips them to navigate life's challenges more effectively. Ultimately, it contributes to a deeper understanding of emotion regulation in education and paves the way for further research in this field.